2023
DOI: 10.3390/nu15184044
|View full text |Cite
|
Sign up to set email alerts
|

A Naturally Derived Watercress Flower-Based Phenethyl Isothiocyanate-Enriched Extract Induces the Activation of Intrinsic Apoptosis via Subcellular Ultrastructural and Ca2+ Efflux Alterations in an In Vitro Model of Human Malignant Melanoma

Sotiris Kyriakou,
Louiza Potamiti,
Nikoletta Demosthenous
et al.

Abstract: The aim of the current study was to (i) extract isolated fractions of watercress flowers enriched in polyphenols, phenethyl isothiocyanate and glucosinolates and (ii) characterize the anticancer mode of action of non-lethal, sub-lethal and lethal concentrations of the most potent extract fraction in primary (A375) and metastatic (COLO-679) melanoma cells as well as non-tumorigenic immortalized keratinocyte (HaCaT) cells. Cytotoxicity was assessed via the Alamar Blue assay, whereas ultrastructural alterations i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 83 publications
0
3
0
Order By: Relevance
“…For this reason, the activity of SOD, CAT, GPx, GR and GST to metabolize ROS was studied. To this end, A375 cells were subjected to PhEF at non-toxic (below EC 50 ; 0.75% v/v), sub-toxic (at EC 50 ; 1.75% v/v) and toxic (above EC 50 ; 2.5% v/v) concentrations as previously characterized by our group [15]. Overall, it was shown that SOD activity is proportional to the concentration of both PhEF and PoEF since the highest activity was noticed at their highest concentrations (Figure 2B).…”
Section: Evaluation Of Intracellular Antioxidant Capacitymentioning
confidence: 99%
See 2 more Smart Citations
“…For this reason, the activity of SOD, CAT, GPx, GR and GST to metabolize ROS was studied. To this end, A375 cells were subjected to PhEF at non-toxic (below EC 50 ; 0.75% v/v), sub-toxic (at EC 50 ; 1.75% v/v) and toxic (above EC 50 ; 2.5% v/v) concentrations as previously characterized by our group [15]. Overall, it was shown that SOD activity is proportional to the concentration of both PhEF and PoEF since the highest activity was noticed at their highest concentrations (Figure 2B).…”
Section: Evaluation Of Intracellular Antioxidant Capacitymentioning
confidence: 99%
“…In addition, PEITC was shown to induce anticancer potency in various cancer types including cervical, breast, lung, prostate, melanoma and leukemia [10][11][12][13][14]. Recently, a study demonstrated that a naturally derived watercress flowers-based PEITC-enriched extract (PhEF) was capable of inducing the activation of intrinsic apoptosis via subcellular ultrastructural alterations and perturbations in Ca 2+ efflux in malignant melanoma [15]. Furthermore, it appears that the PEITC-induced cytotoxicity was associated with its electrophilic carbon center which can react with cellular nucleophiles (e.g., thiols and amines) to form thiocarbamates/dithiocarbamates and thioureas [16,17].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation